Quality of Life Among Diabetes Mellitus Patients in Indonesian Chronic Disease Management Program (Prolanis) - Tri Ani Marwati; Nur Aini Kusmayanti; Rosyidah Rosyidah (Universitas Ahmad Dahlan, 2022)
Background: International Diabetes Federation (IDF) data shows that the increasing prevalence of diabetes mellitus worldwide is still happening and is a significant global health challenge. Patients with diabetes mellitus tend to have a poorer quality of life than those without a chronic disease. This study aims to obtain an overview of the quality of life of patients with diabetes mellitus. Method: This research was a quantitative descriptive study with a cross-sectional approach, conducted in July–October 2021 at one of the Chronic Disease Management Program Communities (Prolanis) in Bantul District, Yogyakarta. The total participants of this study were 63 patients with diabetes mellitus who were registered in the Prolanis community; they did not show mental disorders and were willing to participate in the study. We used purposive sampling to recruit the participants. Researchers used the WHOQOL-BRIEF questionnaire that has been standardized and created by WHO. Other variables recorded in this study include eating patterns and socio-demographic characteristics. A descriptive analysis was conducted to present the results in tables and graphs. Results: Most participants were elderly (over 50 years old), had a high level of education, had good religious spirituality, were in marital status, and had no comorbidity. Patients with diabetes mellitus in the Prolanis group had a good quality of life and level of life satisfaction. The description of the participants' eating patterns was also good, where none of them consumed instant food anymore, and all consumed a variety of fruits and vegetables regularly. Conclusion: This study showed the quality and satisfaction of life and a good diet in patients with diabetes mellitus in the Prolanis Community. Therefore, it is necessary to advance the Prolanis community to maintain the quality of life, life satisfaction, and lifestyle of patients with diabetes mellitus.